Real‐world re‐treatment outcomes of direct‐acting antiviral therapy failure in patients with chronic hepatitis C. Issue 8 (13th April 2021) - Elhence, Anshuman; Singh, Achintya; Anand, Abhinav; Kumar, Ramesh; Ashraf, Anzar; Kumar, Sonu; Pradhan, Dibyabhaba; Pathak, Piyush; Vaishnav, Manas; Rajput, Mahendra Singh; Banyal, Vikas; Nayak, Baibaswata; et al.
Abstract: Direct‐acting antiviral (DAA) drugs are associated with high (>95%) sustained virological response at 12 weeks (SVR12) in chronic hepatitis C (CHC) patients. There is a paucity of data regarding the characteristics and re‐treatment outcomes of DAA treatment failure patients. In a retrospective analysis of the prospectively collected database, we assessed the outcomes of re‐treatment among patients with previous DAA failure. Patients' characteristics, viral characteristics, including resistance‐associated substitutions (RAS) in a subgroup of patients, SVR12, and clinical outcomes were studied. Of 40 patients with DAA failure, among whom 36 were retreated, mean age was 45.7 years, 63.9% ( n = 23) were male, 63.9% ( n = 23) had a genotype‐3 infection and 63.9% ( n = 23) were cirrhotic. The re‐treatment regimens included a combination of pan‐genotypic DAA, mainly sofosbuvir and velpatasvir with or without ribavirin. Three patients who declined retreatment and one who was still on treatment was excluded. For patients who completed re‐treatment, SVR12 was 100% irrespective of genotypes. SVR12 among genotype 3 was 75% (15 of 20) when lost to follow‐up was considered a treatment failure. Six patients died due to liver‐related causes, including five (83.3%) with hepatocellular carcinoma. RAS analysis in 17 randomly selected patients did not reveal any dominant substitutions in NS5A or NS5B region affecting SVR12, though several novel mutations were observed. In conclusion, re‐treatment of CHC patients with prior DAA failure using pan‐genotypic DAA is associated with high SVR12 rates irrespective of genotype or the presence of RAS.